Yayoi Kusama as a migrant artist an artistic trajectory as a model for understanding postwar art - Laurberg, Marie (2021)
This chapter argues, a closer investigation of Kusama’s mid-1960s art practice adds new and important piece to the postwar avant-garde story. It demonstrates how Kusama’s institutional engagements and artistic itineraries offer model for the understanding of a broader art system that was network-oriented, ramified, transnational and marked by dawning globalization. The extent to which theatrical elements are at play in Kusama’s practice in mid-1960s is underlined by set of recently rediscovered photographs documenting her activities in Europe at the time. Kusama was central figure in the development of what in art history has been described as the expanded concept of art in the 1960s, term embracing host of experiments by which artists in the period went beyond painting and sculpture opening art to all the things around it.
Keywords: Kusama, Yayoi -- 1929-; Geschichte 1960-1970; Kunst; Globalisierung